2017
DOI: 10.1080/0284186x.2017.1355563
|View full text |Cite
|
Sign up to set email alerts
|

Hodgkin lymphoma in children, adolescents and young adults – a comparative study of clinical presentation and treatment outcome

Abstract: Background: Hodgkin lymphoma (HL) treatment protocols for children, adolescents and young adults traditionally differ, but the biological and clinical justification for this remains uncertain. Material and methods: We compared age-dependent clinical presentation and treatment and outcome for 1072 classical HL patients 0-24 years diagnosed in Denmark (1990Denmark ( -2010 and Sweden (1992Sweden ( -2009 in pediatric (n ¼ 315, Denmark <15 years, Sweden <18 years) or adult departments (n ¼ 757). Distribution of c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
1
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 27 publications
2
17
1
2
Order By: Relevance
“…The present investigation was also inspired by differences in HL treatment dictated by administrative and geographical circumstances, with Swedish children receiving more radiotherapy than Danish children . Interestingly, however, we saw little evidence that these differences were reflected in differences in admissions to inpatient and specialist outpatient care during our follow‐up span.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…The present investigation was also inspired by differences in HL treatment dictated by administrative and geographical circumstances, with Swedish children receiving more radiotherapy than Danish children . Interestingly, however, we saw little evidence that these differences were reflected in differences in admissions to inpatient and specialist outpatient care during our follow‐up span.…”
Section: Discussionmentioning
confidence: 91%
“…Our study cohort has been described previously. 2,17,18 Briefly, through hospital file review and population-based hospital-, cancer-, and lymphoma registers we identified all individuals diagnosed with HL before the age of 25 years in the period 1992-2009 in Sweden and 1990-2010 in Denmark. Available data included information on nationality, gender, date of birth and diagnosis, Ann Arbor disease stage at diagnosis, primary treatment and outcome, and when present and relevant, relapse treatment, and outcome.…”
Section: Study Population Comparators and Settingmentioning
confidence: 99%
See 1 more Smart Citation
“…ЛХ у детей является тем онкологическим заболеванием, которое потенциально излечимо у абсолютного большинства пациентов и характеризуется благоприятным прогнозом. После окончания программной терапии показатели общей выживаемости (ОВ) достигают 90 % [6].…”
Section: Introductionunclassified
“…Рекомендации GPOH-HD-2003 основаны на предшествующих 6 терапевтических исследованиях DAL/GPOH, которые проводились рабочей группой в Германии с 1978 г. Их целями являлись оптимизация подходов к терапии и разработка стандартов лечения классической ЛХ у детей [6,7]. Стоит отметить, что пациенты с вариантом нодулярного лимфоидного преобладания ЛХ (НЛПЛХ) получают терапию согласно рекомендациям EuroNet-Pediatric Hodgkin's Lymphoma Group -проведение ПХТ курсами CVP (циклофосфан, винбластин, преднизолон) [8].…”
Section: Introductionunclassified